Good germs, bad germs: Citizen science and microbiology - Lorimer, J; Hodgetts, T (Portland Press, 2017)
Have you ever wondered about the bacteria that live on your chopping boards? How about those in your sink, or the murky depths of the plughole? And if so, were you thinking only about pathogenic ‘germs’, or also about the wider microbial communities that might persist in your homes? And how does such thinking sit with contemporary understandings of ‘good bacteria’, and the popular discourse that we might be ‘too clean’ for our own good? Taking advantage of recent developments in DNA sequencing, a citizen science project called Good Germs Bad Germs is exploring the ambiguously understood microbial ecologies found in peoples’ kitchens. Working with a small community of public participants, the project is concerned with the questions people ask about bacteria in their homes, and what happens when they work with scientists to find out the answers.